2012
DOI: 10.1002/joc.3439
|View full text |Cite
|
Sign up to set email alerts
|

Synoptic and climatological controls of particulate matter pollution in a Southern Hemisphere coastal city

Abstract: A complex interaction of local meteorology and source characteristics regularly leads to nocturnal smog events during winter in Christchurch, New Zealand. The main focus of this article is on improving understanding of the relationship between atmospheric processes operating at a range of scales that leads to poor air quality in such urban environments. This research therefore aims to provide a quantitative analysis of atmospheric influences on particulate matter pollution in Christchurch across a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…Mid-latitude cyclones migrate under the jet stream, suggesting that jet location may affect air quality, as has been found for decadal time scales (Barnes and Fiore, 2013). A few studies emphasize the role of synoptic meteorology in driving observed daily variations in PM 2.5, developing predictors that encapsulate changes in numerous meteorological variables (Appelhans et al, 2012;Tai et al, 2012aTai et al, , 2012b. These statistical predictors are based upon the most frequent meteorological patterns, which resemble the stagnation-cold front progression just described (Tai et al, 2012a).…”
Section: Black Carbon (Bc)mentioning
confidence: 99%
“…Mid-latitude cyclones migrate under the jet stream, suggesting that jet location may affect air quality, as has been found for decadal time scales (Barnes and Fiore, 2013). A few studies emphasize the role of synoptic meteorology in driving observed daily variations in PM 2.5, developing predictors that encapsulate changes in numerous meteorological variables (Appelhans et al, 2012;Tai et al, 2012aTai et al, , 2012b. These statistical predictors are based upon the most frequent meteorological patterns, which resemble the stagnation-cold front progression just described (Tai et al, 2012a).…”
Section: Black Carbon (Bc)mentioning
confidence: 99%
“…One approach that can be used to bridge the gap between atmospheric scales is to use synoptic weather types (e.g., Isaksen et al, 2016;KĂ€smacher & Schneider, 2011;Matthews et al, 2015;Romolo et al, 2006;Yarnal, 1984), with the Kidson (2000) weather types (Renwick, 2011) providing a time series of 12-hourly synoptic conditions that is suitable for a range of applications in the New Zealand region. Kidson weather types have been used to account for variations in the accumulation and redistribution of snow in mountainous terrain (Purdie et al, 2011;Webster et al, 2015), hydrological flows (McKerchar et al, 2010), and in paleoclimate research (Lorrey et al, 2007(Lorrey et al, , 2014, as well as in a range of other applications outside the snow and glacier hydrology space (e.g., Appelhans et al, 2013;Beentjes & Renwick, 2001;Gibson & Cullen, 2015;Sturman & QuĂ©nol, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Across New Zealand, weather typing procedures have been extensively used to understand the sensitivity of local climate variability (and associated impacts) to the larger-scale circulation better. The 'Kidson weather types' (KTs) (Kidson, 2000;Renwick, 2011) have been most commonly applied, with applications including particulate matter air pollution (Appelhans et al, 2013), quantitative fisheries (Beentjes and Renwick, 2001), viticulture (Sturman and QuĂ©nol, 2013), renewable energy assessments (Gibson and Cullen, 2015), snow accumulation and distribution in mountainous terrain (Purdie et al, 2011;Webster et al, 2015), hydrological flows (McKerchar et al, 2010) and paleoclimate research (Lorrey et al, 2007(Lorrey et al, , 2014. Many of these studies have been motivated by the need to understand the sensitivity of the particular application to weather/climate variability as an introductory step to understanding climate change impacts (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies have been motivated by the need to understand the sensitivity of the particular application to weather/climate variability as an introductory step to understanding climate change impacts (e.g. McKerchar et al, 2010;Appelhans et al, 2013;Sturman and QuĂ©nol, 2013).…”
Section: Introductionmentioning
confidence: 99%